A systematic review and thematic synthesis of qualitative research studies on factors affecting safe food handling at retail and food service. (July 2018) - Thaivalappil, Abhinand; Waddell, Lisa; Greig, Judy; Meldrum, Richard; Young, Ian
Abstract: Foodborne disease outbreaks are frequently associated with improper food handling at retail and food service settings, indicating a need to improve food safety practices among food handlers. Many qualitative research studies have been conducted to examine food handlers' opinions, perspectives, and experiences with safe food handling in an effort to understand the factors associated with their use of such practices. The aim of this systematic review was a synthesis of the findings from relevant studies to identify the main across-study themes and develop recommendations for interventions and future research. The following steps used to conduct the review were developed a priori as part of the study protocol: a comprehensive search strategy; relevance screening of abstracts; relevance confirmation of articles; study quality assessment; data extraction; thematic synthesis of results; and quality-of-evidence assessment. We identified 28 relevant articles reporting on 26 unique studies. Behavioural determinants were grouped according to constructs from the Theoretical Domain Framework, and further mapped onto the COM-B model of the Behaviour Change Wheel. A total of 13 categories of determinants of safe food handling were identified. Of these categories, overall confidence ratings were assigned and rated as high (n = 9) and moderate (n = 4). The analysis revealed that: 1) food handlers typically demonstrated good knowledge and had positive attitudes toward training; 2) environmental factors (e.g. policies, resources), reinforcement (e.g. posters, reminders), emotions (e.g. stress), and social influences played a significant role in food handlers' intentions and practices; 3) food handlers were confident in their abilities and showed positive beliefs relating to consequences of unsafe food handling; 4) they demonstrated a lack of motivation to perform safe food handling practices and experienced lapses in concentration; and 5) culturally diverse food handlers had unique barriers such as language and communication. Areas for future research and recommendations for policy and practice are discussed.